Effect of GLP-1 receptor agonist, liraglutide, on muscle in spontaneously diabetic torii fatty rats. (1st January 2022) - Yamada, Shohei; Ogura, Yuji; Inoue, Kazuho; Tanabe, Jun; Sugaya, Takeshi; Ohata, Keiichi; Nagai, Yoshio; Natsuki, Yasunori; Hoshino, Seiko; Watanabe, Shiika; Ichikawa, Daisuke; Kimura, Kenjiro; et al.
Abstract: This study investigated the effect of liraglutide, a glucagon-like peptide-1 receptor agonist, on skeletal muscles in rats with type 2 diabetes. Male SDT fatty rats (8-week-old) were provided liraglutide, or insulin-hydralazine for 8 weeks; control SDT fatty rats and SD rats were administered a vehicle. At 16 weeks of age, muscle strength of limbs was significantly lower in all SDT fatty rats compared to SD rats. While cross-sectional areas of type IIb muscle fibers in extensor digitorum longus muscle were significantly lower in SDT fatty rats than in SD rats, those of type I muscle fibers in soleus were similar in all rats. In the soleus of SDT fatty rats, liraglutide led to greater citrate synthase activity and cytochrome c oxidase subunit 5 B protein expression, independently of blood glucose and blood pressure levels. Liraglutide may contribute to preservation of mitochondrial content on soleus muscle in type 2 diabetes. Highlights: Liraglutide increased citrate synthase activity on soleus muscle in SDT fatty rats. Liraglutide upregulated Cox5B protein expression on soleus muscle in SDT fatty rats. Liraglutide did not provide beneficial effects on EDL muscle in SDT fatty rats. Liraglutide may preserve mitochondrial content on soleus muscle in type 2 diabetes.